EFFICACY OF RECURRENT RITUXIMAB TREATMENT IN PATIENT WITH SEVERE REFRACTORY SYSTEMIC JUVENILE RHEUMATOID ARTHRITIS - E.I. Alexeeva; R.V. Denisova; S.Yu. Morev; О.О. Malakhov; О.А. Malakhov ("Paediatrician" Publishers LLC, 2011)
The article contains clinical case description of a severe systemic juvenile rheumatoid arthritis, that was refractory to classic immunosuppressant therapy. The disease was characterized by such extraarticular manifestations as fever, lymphadenopathy,  hepatosplenomegaly, polyserositis, generalized joint involvement and high activity in lab tests. As a result of severe clinical course of the disease, patients develop bilateral aseptic bone necrosis in coxofemoral joints and coxarthrosis. Against the background of glucocorticosteroid treatment the patient has developed hormone-dependency and hormone resistance. Inclusion into the treatment of anti-CD20 monoclonal antibodies (rituximab) has stopped systemic manifestations of the disease, inflammation in the joints, normalized lab activity rates. The positive therapeutic effect allowed to perform surgery due to bilateral coxarthrosis. These results show that rituximab is highly effective in children with systemic juvenile rheumatoid arthritis, that is resistant to classic immunosupressants and glucocorticoides. Key words: children, systemic juvenile rheumatoid arthritis, rituximab, recurrent treatment, prosthetics, hip joint. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 157-163.)